2015
DOI: 10.1371/journal.pone.0141479
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells in Aggregate Form to Enhance Chondrogenesis in Hydrogels

Abstract: There are a variety of exciting hydrogel technologies being explored for cartilage regenerative medicine. Our overall goal is to explore whether using stem cells in an aggregate form may be advantageous in these applications. 3D stem cell aggregates hold great promise as they may recapitulate the in vivo skeletal tissue condensation, a property that is not typically observed in 2D culture. We considered two different stem cell sources, human umbilical cord Wharton’s jelly cells (hWJCs, currently being used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
(40 reference statements)
0
19
0
Order By: Relevance
“…[44] Recently, Li et al generated supramolecular polypeptide-DNA hydrogels and used them for the first time for in situ multilayer 3D bioprinting. [45] Furthermore, double network hydrogels were generated consisting of a DNA hydrogel and phenylalanine-functionalized carboxymethyl cellulose and cucurbit [8]uril (CB [8]). [46] Using this strategy, the structure and mechanical characteristics of the hydrogel could be maintained by the first network over longer period, whilst the second network (DNA hydrogel) is selectively degraded e.g., by specific enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…[44] Recently, Li et al generated supramolecular polypeptide-DNA hydrogels and used them for the first time for in situ multilayer 3D bioprinting. [45] Furthermore, double network hydrogels were generated consisting of a DNA hydrogel and phenylalanine-functionalized carboxymethyl cellulose and cucurbit [8]uril (CB [8]). [46] Using this strategy, the structure and mechanical characteristics of the hydrogel could be maintained by the first network over longer period, whilst the second network (DNA hydrogel) is selectively degraded e.g., by specific enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that human second passage IPFP-ASC into the third passage IPFP-ASC requires approximately 48-60 h [26,36,38]. The total number of cells has a certain effect on cell proliferation capability, which may be related to intercellular communication and microenvironment [40,41]. We should pay attention to these factors in order to 3 Stem Cells International obtain more stem cells with strong proliferation capacity.…”
Section: Isolation Culture Identification and Differentiation Potementioning
confidence: 99%
“…Moreover, 3D spheroid culture improved the survival of stem cells after transplantation by upregulating the anti-apoptotic factor, Bcl-2, and downregulating other apoptotic factors such as Bcl-2-associated X protein (BAX) [17,18]. Additionally, 3D spheroid formation enhanced the therapeutic potential of spheroid MSCs as increases have been observed in their angiogenic, anti-inflammatory, and immunomodulatory properties [16,17,[19][20][21].Recently, the application of aggregated adipose-derived stem cells (ACSC), bone marrow-derived stem cells (BMSCs), and Wharton's jelly cells (WJCs) from umbilical cord demonstrated increased osteogenic and chondrogenic activity in osteochondral disease models [22][23][24][25][26]. Additionally, preclinical animal studies, whereby animals received transplantation of 3D spheroid UCB-MSCs in cases of liver disease, have reported increases of hepatic differentiation.…”
mentioning
confidence: 99%
“…Recently, the application of aggregated adipose-derived stem cells (ACSC), bone marrow-derived stem cells (BMSCs), and Wharton's jelly cells (WJCs) from umbilical cord demonstrated increased osteogenic and chondrogenic activity in osteochondral disease models [22][23][24][25][26]. Additionally, preclinical animal studies, whereby animals received transplantation of 3D spheroid UCB-MSCs in cases of liver disease, have reported increases of hepatic differentiation.…”
mentioning
confidence: 99%